Reuse of water for the production of seedlings of pine cone (Research, Society and Development, 2020)
This study aimed to evaluate the utilization of air conditioning and agroindustrial effluent in the production and development of pine cone seedlings. The research was developed in the seedling production sector of the Federal Institute of Paraiba, Campus Sousa. The experimental design was completely randomized, with four treatments and four replications. The treatments consisted of four water proportions: T1 = 100% of artesian well; T2 = 100% of air conditioning; T3 = 50% air conditioning + 50% agroindustrial effluent; T4 = 100% agroindustrial effluent. The pine cone seedlings were produced in polyethylene bags, using as soil substrate and bovine manure in proportion (2:1 v. V). The following variables were evaluated: number of Leaves (NF), stem diameter (DC), dry matter of the aerial part and root dry and the influence on soil attributes such as the potential of hydrogenionic (pH), phosphorus (P), potassium (K +), sodium (Na +), calcium (Ca + 2), Magnesium (Mg + 2), Sum of bases (SB), percentage of exchangeable sodium (PST) and organic matter (M. O).  The treatments T1 and T2 are viable alternatives for the use in irrigation of seedlings of pine cone. The T4 treatment is not recommended for irrigation of pine cone seedlings due to the toxicity level caused by the high levels of sodium and chloride.